Jack of Fables. [4], Americana - Willingham, Bill (DC Comics, 2008)
Jack hits the road in search of a lost city of gold. Aided by his sidekicks Paul Bunyan, Humpty Dumpty, Gary the pathetic fallacy and the mysterious Hillary Page, Jack's in for the adventure of a lifetime! --publisher's website.